Analisis Yuridis Tindak Pidana Pelaku Pengeroyokan Terhadap Pelaku Kecelakaan Lalu Lintas Di Kabupaten Kupang - Dethan, Grace; Tallo, Daud Dima; Dima, Andrianus Djara (Law Faculty, Nusa Cendana University, 2024)
This study examines the legal analysis of the crime of ganging up on traffic accident perpetrators in Kupang Regency. The background of this study is based on the high number of violent crimes that occur in Indonesia, even though this country was founded on the basis of law as regulated in Article 1 paragraph (3) of the 1945 Constitution. Based on the background of this study, two problem formulations were found (1) How is the legal review of traffic accidents according to Law No. 22 of 2009 concerning Traffic and Road Transportation? (2) What are the legal consequences for perpetrators of ganging up on traffic accidents according to the Criminal Code. This study aims to reveal the legal review of traffic accidents according to Law No. 22 of 2009 and analyze the legal consequences for perpetrators of ganging up on traffic accidents based on the Criminal Code (KUHP). The research methods used include field research with interviews and library research with a legal and legislative concept analysis approach. The results of the study indicate that cases of ganging up on traffic collision perpetrators often occur due to low legal awareness, the influence of alcohol, and lack of recognition from other perpetrators. This study contributes to the understanding of criminal law, especially related to the handling of ganging up crimes in the context of traffic accidents.